MO349IMPACT OF EARLY FLUID ADMINISTRATION ON INPATIENT MORTALITY AND ACUTE KIDNEY INJURY IN PATIENTS WITH COVID-19 DISEASE. (29th May 2021) - Hendra, Heidy; Sudusinghe, Dinesha; Greenan-Barrett, James; Chowdhury, Melissa; Mathew, David; Rauf, Muhammad Umaid; Karra, Efthimia; Aziz, Umaira; Kostakis, Ioannis D; Sood, Tara; Lamb, Lucy; Masson, Philip; et al.
Abstract: Background and Aims: Initial WHO guidance advised cautious fluid administration for patients with COVID-19 due to concern about the development of acute respiratory distress syndrome (ARDS). However, as the pandemic unfolded it became apparent that patients who were admitted to hospital had high rates of AKI and this initiated a change in local clinical guidelines during early April 2020. We aimed to ascertain the impact of judicious intravenous fluid use on mortality, length of hospitalisation and AKI. Method: An observational cohort study of 158 adults admitted with confirmed SARS-Cov-2 between 18 th March and 9 th May 2020 was conducted in a teaching hospital and designated centre for infectious diseases, London, UK. Key clinical and demographic data collected included clinical severity markers on admission, biochemical and haematological parameters as well as radiological findings. Primary outcomes were inpatient mortality, mortality at 6-weeks post discharge, length of hospitalisation and intensive care (ICU) admission. We also measured requirement for kidney replacement therapy (KRT) and AKI recovery rate at discharge. Using tests of difference, we compared key outcomes between patients treated with varying fluid regimens and then identified risk factors for AKI and mortality using multivariate logistic regression with results expressed as odds ratios (OR) with corresponding 95% confidence interval (CI). Results: The median age was 74.4 (IQR 59.90 - 84.35) years, 66% were male, 53% white with hypertension and diabetes being the commonest co-morbidities. The median duration of illness prior to admission was 7 days (IQR 2 – 10) with respiratory symptoms and fever most prevalent. The people who presented with AKI on admission were more likely to receive fluids (34% vs 15%, p=0.02). 118 patients (75%) received fluids within 24-hours of admission with no difference in volume administered after local guidance change (p=0.78). Comparing patients receiving fluids with those who did not, we observed no difference in mortality (p=0.97), duration of hospital stays (p=0.26) or requirement for ICU admission (p=0.70). 18% died as an inpatient, and 52 patients were either admitted with or developed AKI. Of these 52 patients, 43 received fluids and 9 did not with no difference in KRT requirement (p=0.34), mortality (p=0.50) or AKI recovery (p=0.63). Peak AKI stage was greater among participants who received fluids though stage of AKI at presentation was also greater (p=0.04). Mortality rate in patients with an AKI is higher compared to overall inpatient mortality (31% vs 18%). Of the 36 patients with AKI who were discharged home, 25 patients (69.4%) had renal recovery by the time of discharge. Increasing age and clinical severity on admission were associated with higher mortality (see Figure 1 ) . Older age was associated with 34 - 53 times higher risk of death compared with those aged ≤ 65 years (age 76 - 85 years: OR 34.26, 95% CI: 3.94 - 297.48, p=0.001; age > 85 years: OR 53.07, 95% CI: 5.23 - 539.03, p=0.001). Patients with NEWS2 >4 on admission has 5-fold increased risk of death than those with a score ≤4 (OR 5.26, 95% CI: 1.32 - 20.92). Black ethnicity was associated with a 16-fold increased risk of developing AKI (OR 15.86, 95% CI: 1.67 - 150.99). Conclusion: To our knowledge, this is the first study to examine the impact of fluid management on inpatient mortality as well as on renal-associated outcomes of COVID-19 admission. Fluid administration regimen did not have an impact on mortality, length of hospitalisation or ICU admission, nor did it affect renal outcomes. Given the high rates of AKI and KRT in COVID-19 disease, early fluid administration is likely to be an important cornerstone of future management. Further adequately powered prospective studies are required to identify whether early fluid administration can reduce renal injury.